How to improve support for people with (complex) multiple-problems through social prescribing in a vulnerable neighborhood; professionals’, experts-by-experience’ and clients’ perspectives - C. Bos; S. Vader; N. van Vooren; K. Jerković-Ćosić; B. Keij (BMC Primary Care)
Abstract Background Comparative analysis of literature on social prescribing implementation suggests that strategies for implementing social prescribing for people with (complex) multiple-problems may differ significantly from those for people with mild-psychosocial issues. Similar findings have been observed in the Netherlands, where a SP program has been developed in 2018. This study examines the perspectives of health and care professionals, experts-by-experience, and clients regarding the design and implementation of social prescribing in vulnerable neighborhoods in order to better support people with (complex) multiple-problems. Methods This study includes the first steps of the participatory action research methodology. During the research, 26 semi-structured interviews and observations were applied to gain insight among professionals, experts-by-experience and clients. Results The findings indicate that support for people with (complex) multiple-problems requires more than a referral to already existing activities and services. Experts-by-experience and clients highlighted the necessity for a tailored based approach that considers clients’ unique circumstances, e.g. the clients’ living environment, particularly for those with (complex) multiple-problems and having a multicultural backgrounds. While all participants recognized the importance of addressing wider health needs, they also identified several challenges in doing so. Key themes for improving the support for individuals with (complex)multiple-problems are related to fragmentation due to insufficient collaboration, and to how wider health needs can best be addressed and by whom. Conclusion While there is a clear willingness to enhance support for people with multiple-problems, findings reveal significant challenges faced by all parties involved. A key issue identified is the mismatch between what clients need and what professionals are able to provide. Ultimately, a tailored approach is essential for effectively addressing the complex and wider health needs of both individuals and populations, in order to improve their overall health and well-being outcomes. This approach may be feasible by providing clients with (complex) multiple-problem with a single case manager as first point of entry.